2015
DOI: 10.1074/jbc.m115.689596
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Functional O-Linked N-Acetylglucosamine (O-GlcNAc) System in the Thermophilic Bacterium Thermobaculum terrenum

Abstract: Background: Protein O-GlcNAcylation is essential for function and stability of many proteins in metazoa and is essential for development.Results: Thermobaculum terrenum encodes a functional O-GlcNAc hydrolase and a conserved O-GlcNAc-transferase.Conclusion: T. terrenum is the first known bacterium to possess the components for a functional O-GlcNAc system.Significance: T. terrenum could become a reductionist model to study protein O-GlcNAcylation on an organism level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 69 publications
(102 reference statements)
1
33
0
Order By: Relevance
“…Intriguingly, we found that the glycopeptides bound in the substrate-binding cleft in a bidirectional yet nearly identical conformation. In addition, we noted that the same TAB1 glycopeptide was previously reported as V shaped in bacterial OGA complexes: Cp OGA-TAB1 (PDB: 2YDS) 16 and Tt OGA-TAB1 (PDB: 5DIY) 17 . However, the peptide residues of TAB1 oriented dramatically differently in human OGA from those in the bacterial homologs (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Intriguingly, we found that the glycopeptides bound in the substrate-binding cleft in a bidirectional yet nearly identical conformation. In addition, we noted that the same TAB1 glycopeptide was previously reported as V shaped in bacterial OGA complexes: Cp OGA-TAB1 (PDB: 2YDS) 16 and Tt OGA-TAB1 (PDB: 5DIY) 17 . However, the peptide residues of TAB1 oriented dramatically differently in human OGA from those in the bacterial homologs (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Hence, there is a great interest in understanding how OGA recognizes various substrates and dynamically regulates O-GlcNAc biology. Towards addressing this important question, bacterial OGA homologs have been crystallized 13 , 14 , 18 and two were solved in complex with synthetic glycopeptides 16 , 17 . These studies illustrated how the GlcNAc moiety is anchored by a set of highly conserved residues in OGA catalytic pocket.…”
Section: Discussionmentioning
confidence: 99%
“…Although human OGA was first cloned and biochemically characterized in 2001 [36], it did not yield to structural studies until 2017. In the meantime, studies of bacterial homologs possessing a GH84 domain provided valuable insights into the hydrolytic mechanism and allowed the rational design of potent and specific OGA inhibitors, including GlcNAcstatin and thiamet-G [38][39][40][41][42][43][44].…”
Section: O-glcnacasementioning
confidence: 99%
“…The structural basis for an understanding of human OGA and for the catalytic mechanism of O‐GlcNAc hydrolysis were provided from the crystal structures of four bacterial OGAs that share significant sequence similarity with human OGA in the catalytic domain: Bacteroides thetaiotaomicron hexosaminidase ( Bt GH84), Clostridium perfringens NagJ ( Cp OGA), Oceanicola granulosus glycosidase ( Og OGA), and Thermobaculum terrenum glycoside hydrolase ( Tt OGA) . OGA undergoes a substrate‐assisted catalytic mechanism with net retention of the anomeric configuration by using two key catalytic aspartic acid residues at positions 174 and 175 as a general base and a general acid, respectively, as described in Figure B…”
Section: O‐glcnacase (Oga)mentioning
confidence: 99%